Modelo de Gestión del Talento Humano para mejorar el Clima Laboral del Hotel & SPA Casa Real - Morejón Cabezas, José Javier (2016)
The following research is aimed at the realization of a Management Model of Human talent for the Casa real hotel & SPA located in the city of Riobamba, which in turn will support to the processes of human talent that are currently affecting to the correct development of employees, as far as the improvement of the workforce of employees, since they are the main protagonists of the service offered in the hotel establishment and therefore the customer satisfaction. A situational analysis of the hotel establishment was performed in this research by means of the problem and analysis tree SWOT; where it was highlighted a number of shortcomings related to staff training, selection processes and hiring staff, evaluations of job performance and Human Resources planning. All these causes are the result of the absence of a management model of human talent, which affects the development of the work environment of the Casa Real Hotel & SPA. This research was conducted with the total number of employees who are currently working in the hotel establishment, likewise with an interview with the hotel manager; documentary, field and bibliographic research were employed in this kind of study. The results obtained by applying the survey to the internal customers and interview to the Manager of the hotel are linked to the dissatisfaction with respect to the organization of the processes of human talent.